Dipole moments in Langmuir monolayers from aromatic carboxylic acids - Dynarowicz-Latka, P.; Cavalli, A.; Silva, D. A.; dos Santos, M. C.; Oliveira, O. N. (Elsevier B.V., 2000)
The three-layer capacitor model proposed by Demchak and Fort [J. Colloid Interface Sci. 46 (1974) 191] is employed to relate measured surface potentials of Langmuir monolayers from a series of polyphenyl carboxylic acids to molecular dipole moments calculated using semiempirical quantum methods. The effective dielectric constant at the air/monolayer interface is 3.0 +/- 0.6, very close to that estimated for aliphatic compounds. Good agreement between theory and experiment is obtained by adopting a dielectric constant of 6.4 for the monolayer/water interface and a contribution from the water reorientation of -0.064 +/- 0.006 D, which shows that the parameters in the DF model are essentially the same as for aliphatic amphiphiles, such as esters, acids, alcohols and ethers. (C) 2000 Elsevier B.V. B.V. All rights reserved.